(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The modern requirements placed on the education system are increasingly enhancing the importance of individualization as a promising direction in its development. Because individualization makes it possible to create the necessary conditions for the development of human capital — one of the main tasks of educational practice — as well as for consciously understanding one’s activities and demonstrating one’s potential.